OPTIMALISASI PENGGUNAAN FORKLIFT TERHADAP KELANCARAN PROSES BONGKAR STEEL COIL DI PT. DAISY MUTIARA SAMUDRA - SITI SAHARA; Annas Ruli Pradana (Universitas Negeri Jakarta, 2021)
This study aims to analyze the time it takes for a forklift to dismantle the steel coil from the ship's hold to the lossing truck and to find out the number of costs incurred for renting a forklift when carrying out a steel coil unloading activities. The research method used in this research is quantitative by taking into account the comparison of the data used for the cost of using forklifts by buying or staying with existing conditions, namely the rental system. Based on the results of the analysis, it was found that the costs incurred to rent a forklift in January were Rp. 130,200,000, while in February amounting to Rp. 133,800,000. This amount of expenditure is certainly greater than the costs incurred for carrying out forklift maintenance per month. If the company buys 1 unit of 15-ton forklift, the company will save Rp. 7,600,000 - Rp. 12,000,000..